Comparison of venous sinus manometry gradients obtained while awake and under general anesthesia before venous sinus stenting. (15th September 2016) - Fargen, Kyle M; Spiotta, Alejandro M; Hyer, Madison; Lena, Jonathan; Turner, Raymond D; Turk, Aquilla S; Chaudry, Imran
Abstract : Introduction: Venous sinus stenting is a popular treatment strategy for patients with high venous sinus pressure gradients across a site of outflow obstruction. Little is known about the effect of anesthesia on venous sinus pressure measurements. Objective: To compare venous manometry performed in patients under general anesthesia and while awake. Methods: A prospective database was accessed to retrospectively identify patients who had undergone venous sinus stenting. Pressure gradients were compared between those patients who underwent manometry while awake and before stenting under general anesthesia. Results: Thirty patients with both general anesthesia and awake pressure recordings were identified. Pressure measurements were highly variable but overall were higher under general anesthesia by an average of 5.8 mm Hg (1.7; p=0.002). A significant difference between awake and general anesthesia pressure measurements was detected in the sigmoid sinus (5.8 mm Hg (2.0); p=0.005) and the jugular vein (8.1 mm Hg (3.9); p=0.040). Only 11/30 (36.7%) pressure gradients remained within 5 mm Hg of the original awake gradient when repeated under general anesthesia; 9/30 (30%) patients had gradients that were at least 10 mm Hg different across procedures. Conclusions: Calculated pressure gradients were markedly affected by anesthesia. These findings suggest that candidacy for stenting should be determined with venous manometry while patients are awake owing to the unpredictable and highly variable effect of general anesthesia on pressure measurements and an apparent tendency to underestimate the degree of venous outflow obstruction.